Y - x = 6
y + 2x = 57
2y - 2x =12
y + 2x = 57
∴3y = 69
y = 23
23 - x = 6
-x = -17
x =17
large van = 23
small van = 17
Answer:
Around 8 days
Step-by-step explanation:
Divide 325 from 2,563
2563 / 325 = 7.888
Round that number
Answer:
143
Step-by-step explanation:
x-31=112
Add 31 to both sides,
x - 31 = 112
+31 +31
-31 and +31, cancel out so we're left with...
x = 143
x is powering both numbers so it can be outside the parenthesis.
We have given that 3^x.
<h3>
What is the expression?</h3>
An expression or mathematical expression is a finite combination of symbols that is well-formed according to rules that depend on the context.
The first one isn't an answer because 3^x is exponential while x^3 is a cubic function.
If you draw them you will see that they are very different.
B is correct because we can divide both numerator and denominator by 6 and we get 3^x.
C is not correct because x is not powering 3 so we cannot divide both by 6D is correct because 3^(x-1) is the same as
and when multiplied by 3 we get 3^x
3^x*3^(-1) = 3^x/3
E is not correct.
will understand after the explanation in DF is correct.
x is powering both numbers so it can be outside the parenthesis.
The question is incomplete the complete question is,
Which expressions are equivalent to the one below? Check all that apply.
3^x
A. x^3
B.(18/6)^x
C.18^x/3
D.3(3^(x-1))
E.3(3^(x+1))
F.18^x/6^x
To learn more about the expression visit:
brainly.com/question/723406
#SPJ1
Answer:
The answer is
![sin(\theta)=-\frac{\sqrt{2}}{2}](https://tex.z-dn.net/?f=sin%28%5Ctheta%29%3D-%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D)
![tan(\theta)=-1](https://tex.z-dn.net/?f=tan%28%5Ctheta%29%3D-1)
Step-by-step explanation:
we know that
![tan(\theta)=\frac{sin(\theta)}{cos(\theta)}](https://tex.z-dn.net/?f=tan%28%5Ctheta%29%3D%5Cfrac%7Bsin%28%5Ctheta%29%7D%7Bcos%28%5Ctheta%29%7D)
![sin^{2}(\theta)+cos^{2}(\theta)=1](https://tex.z-dn.net/?f=sin%5E%7B2%7D%28%5Ctheta%29%2Bcos%5E%7B2%7D%28%5Ctheta%29%3D1)
In this problem we have
![cos(\theta)=\frac{\sqrt{2}}{2}](https://tex.z-dn.net/?f=cos%28%5Ctheta%29%3D%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D)
![\frac{3\pi}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Cpi%7D%7B2%7D%20%3C%5Ctheta%20%3C%202%5Cpi)
so
The angle
belong to the third or fourth quadrant
The value of
is negative
Step 1
Find the value of ![sin(\theta)](https://tex.z-dn.net/?f=sin%28%5Ctheta%29)
Remember
![sin^{2}(\theta)+cos^{2}(\theta)=1](https://tex.z-dn.net/?f=sin%5E%7B2%7D%28%5Ctheta%29%2Bcos%5E%7B2%7D%28%5Ctheta%29%3D1)
we have
![cos(\theta)=\frac{\sqrt{2}}{2}](https://tex.z-dn.net/?f=cos%28%5Ctheta%29%3D%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D)
substitute
![sin^{2}(\theta)+(\frac{\sqrt{2}}{2})^{2}=1](https://tex.z-dn.net/?f=sin%5E%7B2%7D%28%5Ctheta%29%2B%28%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D%29%5E%7B2%7D%3D1)
![sin^{2}(\theta)=1-\frac{1}{2}](https://tex.z-dn.net/?f=sin%5E%7B2%7D%28%5Ctheta%29%3D1-%5Cfrac%7B1%7D%7B2%7D)
![sin^{2}(\theta)=\frac{1}{2}](https://tex.z-dn.net/?f=sin%5E%7B2%7D%28%5Ctheta%29%3D%5Cfrac%7B1%7D%7B2%7D)
------> remember that the value is negative
Step 2
Find the value of ![tan(\theta)](https://tex.z-dn.net/?f=tan%28%5Ctheta%29)
![tan(\theta)=\frac{sin(\theta)}{cos(\theta)}](https://tex.z-dn.net/?f=tan%28%5Ctheta%29%3D%5Cfrac%7Bsin%28%5Ctheta%29%7D%7Bcos%28%5Ctheta%29%7D)
we have
![sin(\theta)=-\frac{\sqrt{2}}{2}](https://tex.z-dn.net/?f=sin%28%5Ctheta%29%3D-%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D)
![cos(\theta)=\frac{\sqrt{2}}{2}](https://tex.z-dn.net/?f=cos%28%5Ctheta%29%3D%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D)
substitute
![tan(\theta)=\frac{-\frac{\sqrt{2}}{2}}{\frac{\sqrt{2}}{2}}](https://tex.z-dn.net/?f=tan%28%5Ctheta%29%3D%5Cfrac%7B-%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D%7D%7B%5Cfrac%7B%5Csqrt%7B2%7D%7D%7B2%7D%7D)
![tan(\theta)=-1](https://tex.z-dn.net/?f=tan%28%5Ctheta%29%3D-1)